2014
DOI: 10.1111/jbi.12446
|View full text |Cite
|
Sign up to set email alerts
|

A diverse alpine species pool drives a ‘reversed’ plant species richness–elevation relationship in interior Alaska

Abstract: Aim We evaluate whether vascular plant species richness in interior Alaska is highest in the alpine zone. We test the proposition that historical dynamics have influenced the sizes of species pools inhabiting different segments of the landscape by quantifying the contrasting responses of five phytogeographical elements within the flora to changes in elevation and topography. Location Denali National Park and Preserve, Alaska, USA. Methods We developed Bayesian hierarchical models for total plant species richne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 15 publications
(49 citation statements)
references
References 34 publications
4
45
0
Order By: Relevance
“…Only two species were present in four or more plots in 1958, but absent from the sample in 2012 (species “lost”; Table ), whereas eight species that occurred in four or more of the 35 full plots measured in 2012 were not observed in the 1958 full plots (species “gained”; Table ). The two species lost from the sample are alpine taxa, whose minimum elevations in the Denali systematic sample (Roland and Schmidt ) were higher than the study area and mean elevations were much higher (Table ). In contrast, the eight species that were new to the sample in 2012 all had minimum elevations more than 300 m below the elevation of our study area in the same systematic plot data set (Table ).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Only two species were present in four or more plots in 1958, but absent from the sample in 2012 (species “lost”; Table ), whereas eight species that occurred in four or more of the 35 full plots measured in 2012 were not observed in the 1958 full plots (species “gained”; Table ). The two species lost from the sample are alpine taxa, whose minimum elevations in the Denali systematic sample (Roland and Schmidt ) were higher than the study area and mean elevations were much higher (Table ). In contrast, the eight species that were new to the sample in 2012 all had minimum elevations more than 300 m below the elevation of our study area in the same systematic plot data set (Table ).…”
Section: Resultsmentioning
confidence: 96%
“…We compiled the minimum and mean elevational range of these species in Denali, as quantified by a randomized landscape‐scale systematic plot vegetation data set (Roland et al. , Roland and Schmidt ) to investigate the elevational distribution of vascular plant species lost from the 1958 sample or gained in the 2012 sample.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study in interior Alaska revealed that alpine areas support larger vascular plant species pools across multiple scales than do adjacent lowland areas (Roland and Schmidt ). Similar studies in Scandinavia show decreasing and “humped” relationships between vascular plant species pools and elevation, with highest diversity occurring at mid‐elevations (Grytnes et al.…”
Section: Introductionmentioning
confidence: 99%
“…Topography was regarded as the important factor for governing the biodiversity pattern at landscape and regional scales [3][4][5]. Topographic variables, such as altitude, slope and aspect, were often used as predictors to analyze the biodiversity-topography association [6][7][8][9][10]. In recent years, instead of incorporating topographic metrics as predictors to analyze the relationship between species richness and topography, geodiversity was used as a comprehensive indicator to represent environmental heterogeneity [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…However, there still exist conflicting views on the relations between species richness and topographic variables. For example, at least three patterns of species richness along altitude were reported: negative [6,15], positive [16,17] and hump-shaped [7][8][9][10]18]. Recently, some research works provided quantitative proof to underpin positive Environmental Heterogeneity (EH) -species richness relationships across EH subject areas, habitat types, taxonomic groups and …”
Section: Introductionmentioning
confidence: 99%